2014
DOI: 10.1021/bi500356c
|View full text |Cite
|
Sign up to set email alerts
|

Factor Defining the Effects of Glycine Betaine on the Thermodynamic Stability and Internal Dynamics of Horse Cytochrome c

Abstract: A compatible osmolyte such as glycine betaine (GB) and low concentrations of a denaturant constrain the internal dynamics of natively folded carbonmonoxycytochrome c (NCO) at pH 7.0. GB and subdenaturing concentrations of guanidine hydrochloride (GdnHCl) or urea have a cumulative effect on the constrained dynamics of NCO. At higher denaturant concentrations, large-scale unfolding fluctuations dominate the dynamics and inclusion of GB opposes the structural fluctuations that cause unfolding of the protein. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 114 publications
0
9
0
Order By: Relevance
“…64,65 Furthermore, due to charge−π interactions, betaine favorably interacts with the aromatic residues (Trp and Phe) of BM. 9,26 Besides, BM possesses net positive charge on its surface at physiological pH (pI of BM > 7), thereby, more betaine molecules may favorably bind to the surface of the protein through direct interactions with the Lys, Arg, His, or the N−H group of the peptide bond as well as through some indirect interactions. 9,26 With increase in the concentration of betaine, there may be no more water molecules available to hydrate betaine molecules and less water is there for competition with betaine for the protein surface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…64,65 Furthermore, due to charge−π interactions, betaine favorably interacts with the aromatic residues (Trp and Phe) of BM. 9,26 Besides, BM possesses net positive charge on its surface at physiological pH (pI of BM > 7), thereby, more betaine molecules may favorably bind to the surface of the protein through direct interactions with the Lys, Arg, His, or the N−H group of the peptide bond as well as through some indirect interactions. 9,26 With increase in the concentration of betaine, there may be no more water molecules available to hydrate betaine molecules and less water is there for competition with betaine for the protein surface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It should be noted that osmolytes do not cause significant changes in the structures of native proteins [57,82,83]. However, osmolytes are capable of influencing the dynamics of structural changes of native proteins by reducing the heterogeneity of the distribution of the protein conformers in solution [84][85][86][87][88]. In turn, the introduction of osmolytes into solutions that contain denatured or partially denatured proteins results in the compaction of protein structure and decreases the diversity of its conformations [65,[89][90][91][92].…”
Section: Protein Folding In Osmolyte Solutionsmentioning
confidence: 99%
“…This essentially suggests that trehalose protects the folded state from unfolding via the excluded volume effect. Additionally, a recent study by Jain et al 16 hypothesized that the ability of the osmolyte glycine betaine (GB) to counteract the destabilizing effect of chemical denaturants and temperature changes on ferricytochrome c and ferrocytochrome c is partially the result of zwitterionic GB being excluded from the protein surface in much the same way as TMAO. Moreover, using MD simulations, Zhou and coworkers 17 observed that in the presence of guanidinium chloride (GdmCl), urea actually induced a crowding effect on two proteins, hen egg-white lysozyme and protein L, causing them to collapse.…”
Section: Nano-crowding Arising From Solventsmentioning
confidence: 99%